Enhanced structural, optical, and photocatalytic activity of novel Cd–Zn co-doped Mg0.25 Fe1.75O4 for degradation of RhB dye under visible light irradiation. Issue 11 (1st June 2022) - Tanveer, M.; Nisa, Iqra; Nabi, Ghulam; Shakil, M.; Khalid, Syed; Qadeer, M.A.
Abstract: Cdx Zn1-x Mg0.25 Fe1.75 O4 (where x = 0.00, 0.25, 0.50, 0.75, 1.00) have been successfully produced by a facile hydrothermal technique for a thorough comparison of structural, optical, and photocatalytic properties (degradation of Rhodamine B -RhB dye under visible light irradiation). X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM) confirmed the formation of cubic spinel structure for all of the samples. Fourier transform infrared (FTIR) spectroscopy verified the presence of metal-oxygen (M–O) bonding in the prepared samples with two frequency bands corresponding to phonon vibrational stretching in both the octahedral and tetrahedral lattice positions. UV–Visible Spectrophotometer and photoluminescence (PL) spectroscopy investigated the bandgap variation (2.7 eV-1.7 eV) and emission spectrum peaks appearing in the range of 405–471 nm region. The comparison in the photo-degradation of Rhodamine B (RhB) revealed the superior performance (98% degradation of RhB dye in 80 min having a K value of 0.04966 with excellent reusability) of Cd0.50 Zn0.50 Mg0.25 Fe1.75 O4 sample having 50/50 dopant ratio of Cd and Zn in the parent Mg Ferrite, attributed to the lowest bandgap, longer lifetime of charge carriers, active octahedral lattice site, electron/hole pair recombination preventions, and the least value of ohmic impedance at higher frequency.